Collective mental health and social work. A window of opportunity for new social-assistance practices in the field of mental suffering - Serrano-Miguel, Mercedes (Cuadernos de Trabajo Social, 2022)
The aim of this article is to outline the paradigm of collective mental health, which has a long history in Latin America but is merely incipient in Spain, and to show how it can be applied to contemporary social work practice concerning mental health. The article offers a historical and conceptual review of the model and explores its connection with mental health care in Spain by reflecting on three discursive axes: social work in mental health as an emancipatory profession; interdisciplinarity as a practice combining both technical and non-technical knowledge; and understanding and approaching collective mental health from a feminist and intersectional perspective. The overall aim is to provide a potential conceptual framework for new, care-based forms of mental health-related social intervention that contribute to the development of the social work profession in this area.